Gut Microbiota and Metabolite Changes in Patients With Ulcerative Colitis and Clostridioides difficile Infection - Wan, Jian; Zhang, Yujie; He, Wenfang; Tian, Zuhong; Lin, Junchao; Liu, Zhenzhen; Li, Yani; Chen, Min; Han, Shuang; Liang, Jie; Shi, Yongquan; Wang, Xuan; et al. (Frontiers in Microbiology, 2022)
Background Patients with ulcerative colitis (UC) are at an increased risk of developing Clostridioides difficile infection (CDI), which in turn leads to poor outcomes. The gut microbial structure and metabolites in patients with UC and CDI have been scarcely studied. We hypothesized that CDI changes the gut microbiota and metabolites of patients with UC. Methods This study included 89 patients: 30 healthy controls (HC group), 29 with UC alone (UCN group), and 30 with UC and CDI (UCP group). None of the participants has been exposed to antibiotic treatments during the three months before stool collection. Stool samples were analyzed using 16S rRNA gene V3-V4 region sequencing and Gas Chromatography Tandem Time-of-Flight Mass Spectrometry. Results The UCN group displayed lower diversity and richness in gut microbiota as well as a higher relative abundance of the phylum Proteobacteria than the HC group. There were no significant differences between the UCN and UCP groups in the α-diversity indices. The UCP group contained a higher relative abundance of the genera Clostridium sensu stricto, Clostridium XI, Aggregatibacter, Haemophilus, and a lower relative abundance of genera Clostridium XIVb and Citrobacter than the UCN group. In the UCN group, the increased metabolites included putrescine, Maltose, 4-hydroxybenzoic acid, 4-hydroxybutyrate, and aminomalonic acid. Spearman correlation analysis revealed that these increased metabolites negatively correlated with Clostridium XlVb and positively correlated with the four enriched genera. While the correlations between hemoglobin and metabolites were contrary to the correlations between erythrocyte sedimentation rate and high-sensitivity C-reactive protein and metabolites. Conclusions Our study identified 11 differential genera and 16 perturbed metabolites in patients with UC and CDI compared to those with UC alone. These findings may guide the design of research on potential mechanisms and specific treatment for CDI in patients with UC.